2013
DOI: 10.1016/j.celrep.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Choroid-Plexus-Derived Otx2 Homeoprotein Constrains Adult Cortical Plasticity

Abstract: Summary Brain plasticity is often restricted to critical periods in early life. Here, we show that a key regulator of this process in visual cortex, Otx2 homeoprotein, is synthesized and secreted globally from the choroid plexus. Consequently, Otx2 is maintained in selected GABA cells unexpectedly throughout the mature forebrain. Genetic disruption of choroid-expressedOtx2 impacts these distant circuits and in primary visual cortex reopens binocular plasticity to restore vision in amblyopic mice. The potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
247
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(259 citation statements)
references
References 47 publications
12
247
0
Order By: Relevance
“…Choroid plexus-derived Otx2 is widely distributed throughout the brain and is taken up by parvalbumin + neurons, where it regulates the maturation of neural circuitry and critical periods of plasticity in the visual cortex. Blocking release of Otx2 from the choroid plexus in the adult reopens binocular plasticity in the visual cortex [140]. Thus, choroid plexus-derived factors may globally affect neural circuit formation, activity and plasticity during critical periods, as well as in the adult brain.…”
Section: Embryonic and Postnatal Developmentmentioning
confidence: 99%
“…Choroid plexus-derived Otx2 is widely distributed throughout the brain and is taken up by parvalbumin + neurons, where it regulates the maturation of neural circuitry and critical periods of plasticity in the visual cortex. Blocking release of Otx2 from the choroid plexus in the adult reopens binocular plasticity in the visual cortex [140]. Thus, choroid plexus-derived factors may globally affect neural circuit formation, activity and plasticity during critical periods, as well as in the adult brain.…”
Section: Embryonic and Postnatal Developmentmentioning
confidence: 99%
“…Indeed, closing an eye following either protocol can install amblyopia in the adult mouse and, more interestingly, the same protocols restore visual acuity and binocular vision in amblyopic mice [9,30]. Interestingly, reactivation of plasticity was also obtained by hydrolysing the complex sugars present in PNNs [33].…”
Section: Non-cell-autonomous Otx2 Regulates Visual Cortex Plasticitymentioning
confidence: 99%
“…In a collaborative study with the group of Takao Hensch, it was observed that Otx2 content increases in PV cells in parallel with their maturation [29]. Interestingly, this content does not result from local Otx2 expression but from its import from external sources, such as the choroid plexus or, possibly, the retina [29,30].…”
Section: Non-cell-autonomous Otx2 Regulates Visual Cortex Plasticitymentioning
confidence: 99%
See 2 more Smart Citations